Immunoglobulin production by coeliac biopsies in organ culture. Issue 10 (October 1986) - Wood, G M; Shires, S; Howdle, P D; Losowsky, M S
Abstract : The production of immunoglobulins by jejunal mucosa during organ culture has been studied. In 18 untreated coeliac patients the amounts of IgA, secretory IgA and IgM in the culture medium were higher than in those from 17 normal controls. The results in 15 treated coeliac patients did not differ from the control subjects. Mucosal biopsies from patients with serum IgA deficiency produced very little IgA, but large amounts of IgG and IgM. The addition of neither Frazer's gluten fraction III, nor alpha-gliadin to the culture system stimulated any additional increased secretion of immunoglobulins from the untreated coeliac patients. Production of IgA and IgM by the small bowel mucosa continues during organ culture, but that of IgG appears insignificant.